PERTUMBUHAN DAN HASIL TANAMAN MELON (Cucumis melo L.) PADA KOMPOSISI MEDIA TANAM DAN FREKUENSI PEMUPUKAN YANG BERBEDA - Muhammad Iqbal; Faiz Barchia; Atra Romeida (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2019)
[GROWTH AND YIELD OF MELON PLANT (Cucumis melo L.) IN DIFFERENT COMPOSITION OF PLANT MEDIA AND DIFFERENT FREQUENCY OF NPK APPLICATION]. This study aims to determine the best combination of planting media composition and frequency of NPK fertilization on the growth and yield of melon plants. The research was conducted in October 2018 - January 2019 on the land located in Bentiring, Muara Bangkahulu District, Bengkulu City. The design used in this study was a Completely Randomized Design (CRD) consisting of two factors and three replications. The first factor was the composition of the media for plant growth, which consists of three different media composition, namely: sand: soil: manure (30%: 50%: 20%), sand: soil: manure (10%: 60%: 30%), and sand: soil: manure (20%: 70%: 10%). The second factor is the frequency of NPK fertilization consisting of four types of fertilization, namely: 1 time NPK fertilization during planting, 2 times NPK fertilization during planting and 10 days after planting (dap), 3 times NPK fertilization during planting, 10 dap and 20 dap, and 4 times NPK fertilizing during planting, 10 dap, 20 dap and 30 dap. The dose given is 15 g/plant (equivalent to 800 kg/ha) and NPK fertilizer given in the form of compound fertilizer N: P: K 16:16:16. The results showed that the best composition of the planting media was found in the treatment of sand media: soil: manure (10%: 60%: 30%). The best fertilizing frequency was found in the treatment of NPK fertilizing 4 times during planting, 10 dap, 10 dap, 30 dap, and the combination of both produces the most substantial plant length, weight, and fruit circumference